REKONSTRUKSI EPISTEMOLOGI ISLAM SEBAGAI KRITIK TERHADAP HEGEMONI ILMU BARAT SEKULER - Risna Risnawati; Siti Robiah; Ema Maesaroh; Eni Haryani (FKIP Universitas Alwashliyah Medan, 2026)
This journal discusses a critique of secular Western scientific thought, which views knowledge as value-neutral and recognizes truth only based on empirical observation. This perspective has influenced Islamic education in Indonesia, particularly by creating a division between religious knowledge and general knowledge. This problem is evident in the secondary-level Islamic Religious Education (PAI) curriculum, which applies a purely procedural learning approach, thereby failing to fully support the holistic character development of students in accordance with Islamic teachings. This study aims to develop a model for renewing Islamic scientific thinking that can be practically applied to address the influence of secularism in education. The research adopts a qualitative approach through library research. Data are analyzed by interpreting Islamic sources, comparing them with Western modes of thought, and synthesizing them into educational concepts aligned with Islamic values. The results show that the renewal of Islamic scientific thinking must be grounded in Tawhid as the primary foundation, integrating revelation, reason, and empirical experience in the learning process. The proposed model is a Tawhid-based spiral curriculum that connects Islamic Religious Education with general sciences, along with an assessment system that measures not only knowledge but also students’ attitudes and spiritual development through teacher observation, self-reflection, and peer assessment. In conclusion, renewing Islamic scientific thinking is essential for producing knowledge that is beneficial, ethical, and aligned with the core objectives of Islamic teachings. Kata kunci : Rekonstruksi Epistemologi Islam,Tauhid, Dikotomi Ilmu, Pendidikan Agama Islam